PENGOLAHAN LIMBAH KOTORAN TERNAK MENJADI PUPUK KOMPOS DI KECAMATAN PAUH KOTA PADANG - Syaiful, Ferry Lismanto; Novia, Deni; Satria, Benny; Agustin, Fauziah; Sumedi, Sumedi (Jurnal Hilirisasi IPTEKS, 2024)
The management of livestock waste is one of the strategic solutions in overcoming environmental problems while supporting sustainable agriculture. Education on processing livestock manure waste into compost fertilizer is very important to improve the skills of farmers in utilizing livestock waste productively. The purpose of this activity is to provide education to farmers and the community in Pauh District, Padang City, on the technique of processing livestock manure waste into environmentally friendly compost fertilizer. This activity was carried out in livestock group in Pauh District, Padang City. The methods used in this study include socialization, training, and direct assistance to farmers and communities in Pauh District, Padang City. Through a participatory approach, socialization and practical training were conducted to farmers on the process of processing livestock manure waste to produce quality compost. The results of this activity show an increase in the farmers' understanding of livestock waste processing techniques. Moreover, the farmers and community were able to apply these techniques in practice. The use of compost produced from livestock manure waste can reduce dependence on chemical fertilizers which are more expensive and less environmentally friendly. In conclusion, the education on livestock waste management for producing compost fertilizer in Pauh District, Padang, successfully enhanced farmers' knowledge and skills in effectively managing livestock waste, which can contribute to sustainable agriculture.